Surface water pollution caused by phosphate mining development in Mabian Jinyang area, Sichuan Province in 2021: chemical analysis and potential ecological risk index assessment - Tian, Ye; Chen, Zhen; Zhang, Qingui; Lu, Junyong; Wang, Ru; Qin, Ailing; Liu, Qunyi (Frontiers in Earth Science, 2025)
BackgroundThe impact of phosphate mining development on surface water pollution and ecological disasters is a highly concerned issue in global mining activities. With the increasing demand for phosphate fertilizers, the environmental impact of phosphate mining is becoming increasingly prominent, especially in the Mabian Jinyang area of Sichuan Province. This study aims to analyze the mechanisms and impacts of water pollution and ecological disasters caused by phosphate mining development, and evaluate the ecological risks caused by heavy metal pollution in water bodies.MethodWe conducted a systematic assessment of the impact of phosphate mining development on water pollution and ecological risks in the Mabian Jinyang area of Sichuan Province using chemical analysis and potential ecological risk index (PERI) method. The total area of the region is approximately 6,400 square kilometers. We conducted systematic water sample collection and analysis at 367 sampling points from January 2020 to December 2021. By collecting water samples from different work areas, measuring the content of heavy metal elements and total phosphorus in the samples, and quantitatively evaluating the potential threat of heavy metal pollution to the aquatic ecosystem.ResultThe research results show that in the mining work area, both heavy metal element indicators and total phosphorus indicators exhibit point pollution, and the total phosphorus concentration in the water body varies greatly with the seasons. One of the main reasons for the excessive total phosphorus is the collapse caused by geological disasters and the non-standard stacking of slag and gangue piles in the mining development area. In addition, in terms of potential ecological hazards, it is positively correlated with the degree of mining development, and the higher the degree of mining development, the greater the potential ecological hazards. Although the potential ecological hazards of various heavy metals in the water bodies of the work area are not high overall, there are still some areas that exhibit mild to moderate ecological hazards, as well as very few areas with strong ecological hazards. These areas are mainly affected by strong ecological risks caused by Cd and As elements.MeaningThe research findings of this article provide valuable information for mining enterprises and environmental organizations, promoting a balance between phosphate mining and environmental protection, and driving mining activities towards a more sustainable direction. By identifying pollution characteristics and ecological risks, this study provides theoretical support for future environmental management and pollution control measures in mining areas.